IDENTIFIKASI JENIS POHON FAMILI PODOCARPACEAE PADA HUTAN PEGUNUNGAN ATAS DI GUNUNG BAWANG KABUPATEN BENGKAYANG KALIMANTAN BARAT - Ronaldo, Andre; Prayogo, Harri; Muflihati, . (Universitas Tanjungpura, 2019)
Mount Bawang is one of the protected forest areas in Bengkayang Regency, West Kalimantan with an altitude reaching 1.471 masl. Mount Bawang belongs to the type of tropical rain forest which is overgrown by various species of plants with high species diversity. The forest in Gunung Bawang has a zone of upper mountain forest vegetation which is a habitat for tree species from the family Podocarpaceae. Podocarpaceae family tree species can grow in humid forest conditions, dominating the upper mountain forests, mountainous scrublands, and some in the swamp and scorch forest. The purpose of this study was to identify and describe the morphology of tree species from the Podocarpaceae family on Mount Bawang. The method used in this study is an exploration method that is carried out by exploring the ridge at an altitude of 1.100-1.400 masl, then taking samples of the herbarium. Based on the results of the study found 5 species of trees from the family Podocarpaceae. These species are Dacrydium xanthandrum, Falcatifolium falciforme, Podocarpus borneensis, Podocarpus neriifolius, and Phylocladus hyphophyllus. The morphological characteristics of the Podocarpaceae family are generally needle-leafed, leafy mesophyll, thick, upright stems sometimes bent, and have seed-bearing organs in the form of conifers.Keyword: Bengkayang Regency, Mount Bawang, Podocarpaceae, Upper Mountain Forest.